PENGARUH PEMAHAMAN PAJAK, KETENTUAN PERPAJAKAN DAN TRANSPARANSI DALAM PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN PERUSAHAAN JASA KONSULTAN KONSTRUKSI DI KOTA TANJUNGPINANG - Satria, Hendy (An-Nisbah: Jurnal Ekonomi Syariah, 2017)
Abstract: Taxes are compulsory contributions to the state owed by individuals or entities who are forced by law - undnag, by not getting the rewards directly and used for state purposes utuk for - the welfare of the people. This study aims to determine the effect of Understanding Taxes, Taxation Provisions and Transparency in Tax Compliance Against Taxpayer Construction Consulting Services Company in Tanjungpinang. This study uses primary data obtained from questionnaires. The approach used in this research is quantitative data, which is performed with SPSS pass to Understanding Tax, Tax Provisions and Transparency in Tax Compliance Against the taxpayer that can be seen from the questionnaire. Number of samples obtained 64 Construction Consulting Services Company in Tanjungpinang. While data collection techniques in this study were questionnaires and surveys using data analysis methods of scoring, validity, reliability test, classic assumption test, multiple linear regression, t test, F test, the coeffcient of determination. While analysis tools used SPSS 20 to test the classical assumption of normality test, multicollinearity, and test the hypothesis testing heteroskedasitisitas and test them multiple linear regression analysis, t-test, F, and the coeffcient of determination(R2). In general, the analysis indicates that the Understanding Taxes, Rules and Transparency in Taxation Taxation is very infuential on Taxpayer Compliance Consulting Services Construction Company in Tanjungpinang. SPSS can be seen from the test conducted. Most of the tests conducted eligible.Keywords: Understanding of Tax, Tax Provisions and Transparency in Taxation, Taxpayer Compliance Board